EVALUASI PERFORMA JEMBATAN GANTUNG TIPE SUSPENDED PEJALAN KAKI DENGAN LANTAI KACA BERDASARKAN UJI PEMBEBANAN STATIS - Nugraha, Widi; Subrata, Budi; Permadi, Indra Sidik; Sukmara, Gatot; Chairulloh, Achmad Riza; Triwibowo, Hari; Saripudin, Umar (Jurnal Jalan Jembatan, 2023)
The Glass Bridge of Bromo is a suspended type of footbridge with a structural glass floor that was built by the Ministry of Public Works and Public Housing in the Bromo Tengger Semeru National Park, East Java, Indonesia. The bridge was built to provide a unique experience for visitors by allowing them to enjoy the beautiful scenery around Mount Bromo from the transparent floor of the bridge. The use of structural glass as a bridge floor needs to be tested for safety and comfort aspects by testing the load on the structural glass floor segment and the entire bridge structure. Load testing aims to determine whether the bridge is capable of withstanding the load that will pass over it, in this case, pedestrian load. In this study, load testing was carried out on the Glass Bridge of Bromo with an operational planned load of around 100 pedestrians. The load was converted to 240 sandbags with a weight of approximately 35 kg each. The maximum bridge response due to the largest test load was a vertical deformation of 72.70 mm over the entire span, maximum cable force of 19.84 tons, and steel frame stress of the glass floor system of 125.96 MPa. The structural response due to the measured load was well-modeled using the structure model used in this study, allowing for simulation of larger loads for service load evaluation. The analysis results show that the Glass Bridge of Bromo is safe to use with a service load restriction of up to 400 kg/m2. Additionally, the bridge has relatively small deformations compared to the allowable deformation, thus meeting comfort criteria.